Antinociceptive effects, acute toxicity and chemical composition of Vitex agnus-castus essential oil - Emad Khalilzadeh; Gholamreza Vafaei Saiah; Hamideh Hasannejad; Adel Ghaderi; Shahla Ghaderi; Gholamreza Hamidian; Razzagh Mahmoudi; Davoud Eshgi; Mahsa Zangisheh (Mashhad University of Medical Sciences, 2015)
Objective: Vitex agnus-castus (VAC) and its essential oil have been traditionally used to treat many conditions and symptoms such as premenstrual problems, mastalgia, inflammation, sexual dysfunction, and pain. In this study, the effects of essential oil extracted from Vitex agnus-castus (EOVAC) leaves were investigated in three behavioral models of nociception in adult male Wistar rats. Materials and methods: Chemical composition of EOVAC was analyzed using gas chromatography - mass spectrometry (GC-MS) and also its possible toxicity was determined in mice. Analgesic effect of EOVAC was determined using tail immersion test, formalin test, and acetic acid-induced visceral pain in rats. Results: EOVAC (s.c.) and morphine (i.p.) significantly (p